Micro-Hotspots of Risk in Urban Cholera Epidemics. (11th May 2018) - Azman, Andrew S; Luquero, Francisco J; Salje, Henrik; Mbaïbardoum, Nathan Naibei; Adalbert, Ngandwe; Ali, Mohammad; Bertuzzo, Enrico; Finger, Flavio; Toure, Brahima; Massing, Louis Albert; Ramazani, Romain; Saga, Bansaga; et al.
Abstract: Targeted interventions have been delivered to neighbors of cholera cases in major epidemic responses globally despite limited evidence for the impact of such targeting. Using data from urban epidemics in Chad and Democratic Republic of the Congo, we estimate the extent of spatiotemporal zones of increased cholera risk around cases. In both cities, we found zones of increased risk of at least 200 meters during the 5 days immediately after case presentation to a clinic. Risk was highest for those living closest to cases and diminished in time and space similarly across settings. These results provide a rational basis for rapidly delivering targeting interventions.